DESIGN AND DEVELOPMENT OF HYBRID SOLAR E-BIKE FOR SUSTAINABLE GREEN TRANSPORTATION - Asrori, Asrori; Winoko, Yuniarto Agus; Subagiyo, Subagiyo; Eryk, Irwan Heryanto; Udianto, Pondi (Journal of Applied Engineering Science, 2023)
Solar energy has great potential for utilization as an unlimited and alternative renewable energy source that can be stored in batteries and used to drive the BLDC motor on electric bicycles. The purpose of this study was to determine the charging efficiency of a 100 Wp solar panel mounted on an electric bicycle. A solar power meter was used to measure the solar radiation absorbed by the photovoltaic (PV) module, while sensors were used to measure the current and voltage (DC) output from the solar panels. The sensor signals were then processed by a microcontroller and displayed on an LCD screen, as well as recorded by an SD card data logger. The characteristics of the charging voltage were compared with and without the PV module. The results showed that at a solar radiation of 1008 W/m², the maximum voltage and current achieved were 17.49 V and 3.37 A, respectively. Under these conditions, the battery charging efficiency of a 100 Wp solar panel was 58.94%. A one-hour test with an average solar radiation of 976.3 W/m² showed that integrating a 100 Wp PV module increased the energy stored in the e-bike battery by 33.33%. Therefore, the hybrid solar e-bike concept has the potential to improve the performance of electric vehicles in the future.
Keywords: PV-module, e-bike, solar energy, hybrid, charging efficiency